2004
DOI: 10.1021/la035336b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Thermal Condensation Mechanisms of Amino Acids on Oxide Supports. 1. Glycine on Silica

Abstract: Glycine was adsorbed on the surface of a well-defined silica from aqueous solutions of variable concentrations and pHs. The adsorbed molecules were characterized using middle-IR and UV-vis-NIR spectroscopies. Except at the lowest pH (2.0), they were predominantly present on the surface as zwitterions. Two successive deposition mechanisms were evidenced with increasing glycine concentration. At low concentrations, glycine is specifically adsorbed on silica surface sites, probably through its NH3+ moiety. The pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
198
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(218 citation statements)
references
References 38 publications
20
198
0
Order By: Relevance
“…It is worth mentioning that this situation was not observed by Costa et al 556 due to the limited number of water molecules considered. In the work of Rimola et al, 322 the vibrational frequencies of the structure shown in Figure 69e were also computed and compared with the experimental IR results of Meng et al 210 (data shown in Table 16). In this case, the  as (COO -) and (NH 3 + ) modes useful for comparison are hidden by the stretching and bending modes of solvent water, which cover the 3900-3500 cm -1 and 1700-1600 cm -1 regions.…”
Section: Additionally Tpd-ms Experiments (Not Shown Here) Revealed Hmentioning
confidence: 99%
“…It is worth mentioning that this situation was not observed by Costa et al 556 due to the limited number of water molecules considered. In the work of Rimola et al, 322 the vibrational frequencies of the structure shown in Figure 69e were also computed and compared with the experimental IR results of Meng et al 210 (data shown in Table 16). In this case, the  as (COO -) and (NH 3 + ) modes useful for comparison are hidden by the stretching and bending modes of solvent water, which cover the 3900-3500 cm -1 and 1700-1600 cm -1 regions.…”
Section: Additionally Tpd-ms Experiments (Not Shown Here) Revealed Hmentioning
confidence: 99%
“…Amino acids, the components of protein, play an important role in many fields, including food industry and solid-phase peptide synthesis (Meng et al 2004). They are also applied as building blocks for the production of pharmaceutical and agrochemical compounds (O'Connor et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have started to investigate the adsorption of small biological molecules such as amino acids on the same support. 8 Here, we have attempted as a first step to model the adsorption of glycine on silica in conditions of low water activity. For meaningful comparison, experimental results have been obtained by adsorbing glycine from the gas phase.…”
Section: Introductionmentioning
confidence: 99%